Embedded Controlled Isolated Bidirectional Full-Bridge DC-DC Converter with Flyback Snubber. (18th October 2012) - Kirubakaran, D.; Sathi, Rama Reddy
Abstract : An isolated bidirectional full-bridge DC-DC converter with flyback snubber for supplying a resistive load is simulated and experimentally verified. The DC-DC converter for high conversion ratio, high output power, and soft start-up capability is presented in this paper. The circuit consists of a capacitor, a diode, and a flyback converter. These components help to clamp the voltage spikes caused by the current difference between the current fed inductor and leakage inductance of the isolation transformer. The switches are operated by soft-switching technology. The suppression of inrush current which is usually found in the boost mode start-up transition is presented here. The simulated and experimental results for output voltage, output current, and power for both buck and boost modes are presented.